Integrating Islamic Guidance and Counseling to Address Deviant Behavior in Child Victims of Family Violence - Rahmah Rahmah; Nor Fatmah (ALSYS, 2026)
Child abuse in Indonesia produces long-term physical, psychological, and social consequences that may manifest in deviant and aggressive behavior. Although culturally appropriate spiritual care integrated with evidence-based psychotherapy has potential to support recovery, qualitative evidence on such integrated approaches remains limited. This phenomenological study, conducted in Palangka Raya from December 2025 to February 2026, explored how Islamic Counseling Guidance combined with Cognitive Behavioral Therapy (CBT) addressed deviant behavior in a 17-year-old male victim of family violence and identified factors that facilitated or hindered behavioral change. Data were collected through in-depth semi-structured interviews with the subject, caregivers, and counselors, as well as participant and non-participant observations of counseling sessions and daily interactions. Data were analyzed thematically using a phenomenological approach. The intervention integrated spiritual practices and values with CBT techniques, including cognitive restructuring, emotion regulation skills, and behavioral training. During the intervention, the subject demonstrated improved emotion regulation, reduced frequency and intensity of aggressive behavior, clearer emotional expression, and better family communication. Spiritual engagement increased moderately and served as an internal motivator supporting cognitive and behavioral change. Supporting factors included openness, intrinsic motivation, and access to spiritual support, whereas barriers included dysfunctional family dynamics, normalization of violence, economic stress, and the influence of pro-aggressive peers. Temporary relocation to independent living facilities facilitated stabilization. The study concludes that integrated Islamic Counseling Guidance and CBT is feasible and acceptable in the local context, with potential to reduce deviant behavior and strengthen psychosocial and spiritual resources among victims of family violence. However, the sustainability of change remains constrained by family and environmental factors, highlighting the need for multi-level interventions and further empirical research.